Efficiency Use of Nitrogen In Several Palm Oil Varieties With Treatment of Nitrogen Fertilizer Levels In Main Nursery - Muhammad Afrillah; Chairani Hanum; Abdul Rauf (Jurnal Pertanian Tropik, 2018)
Efficiency use of nitrogen in several palm oil varieties with treatment in nitrogen fertilizer level in main nursery. This study aims to determine the growth characteristics of several varieties of palm oil efficient use of nitrogen with the provision of various nitrogen levels in the main nursery. The research was conducted in the nursery area of Yos Sudarso Binjai road and the Soil Laboratory of the Palm Oil Research Center, Medan from May to November 2017, using a factorial randomized block design with two factors. The first factor is varieties consisting of 7 types namely Avros, Simalungun, PPKS 540, Yangambi, PPKS 718, PPKS 239, Langkat. The second factor is the N fertilization dose consisting of 5 levels ie 0, 25, 50, 75 and 100% from fertilizer recommendation. The results showed that the addition of N level increased the dry weight of the canopy, and the uptake of plant N nutrients. The efficient use of optimal Nitrogen in Yangambi varieties was obtained on N 25% fertilization, while Avros and PPKS 239 were at 50% recommendation level. 75% recommendation produce optimal value efficient use of N on Simalungun variety, PPKS 718, and Langkat. PPKS 540 varieties efficient use of N optimal at 100% recommendation level.